Transhumanism in Film - May, Nathaniel (Wake Forest University, 2014)
Technological progress is a defining theme across human history. Man has long relied on technology to influence the world around him. Modern advancements in fields such as neuroscience and robotics present significant ethical challenges to society. The transumanist movement that focuses on the process by which humans transcend their natural limits through technology is at the forefront of these new discoveries. Many of the questions surrounding these technologies are deep, moral dilemmas that have occupied human minds for generations. In an effort to better understand these deep-seated questions, this thesis evaluates transhumanism through the medium of film. Films can act as case-studies by which to discuss the ethical issues at hand. In addition, film connects generations, individuals, and societies - allowing for an exchange of perspectives. I present a number of films that provide insight towards understanding the moral concepts of personhood, moral status, and perfection. I conclude by acknowledging the importance of film as a communication tool by which members of the moral community can grow their understanding of their place within the world.
Keywords: Bioethics; Transhumanism